Analisis Faktor Penyebab Anak Putus Sekolah di Desa Oinlasi Kecamatan Mollo Selatan Kabupaten Timor Tengah Selatan - Ayunda Pratini Tefa; Idris (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
The purpose of this study was to determine the factors that cause children to drop out of school, and the efforts of parents to overcome dropout students in Oinlasi Village, South Mollo District, South Central Timor Regency. This study used the qualitative research method with a purposive sampling technique. The subject of this study were dropout students, parents, and the head of the village. Data collection techniques were carried out through observation, interviews, and documentation. The data analysis technique used interactive analysis, namely data reduction, data display, and data verification. The results showed that the factors that cause children dropout of school were parents’ low economic background, children’s lack of interest to get an education, peer factors, the distance from school. The efforts of parents to overcome dropout students were motivating children, giving advice, and controlling children's activities.